2018
DOI: 10.1371/journal.pone.0192302
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteins in circulating immune complexes are biomarkers of patients with Indian PKDL: A study from endemic districts of West Bengal, India

Abstract: BackgroundPost Kala Azar Dermal Leishmaniasis (PKDL) occurs as dermal consequence of previous Visceral Leishmaniasis (VL) infection and serves as an important reservoir for transmission of VL. Diagnosis of PKDL is often challenging for its symptomatic resemblance to other co-endemic diseases like Leprosy or Vitiligo. Parasitological examination by slit-skin smear and culture are the standard methods but lack high sensitivity. Thus, for efficient control of VL, reliable diagnostic and prognostic assay of PKDL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…This type of assay limits the interaction of antibodies to proteins and glycoproteins, minimizing the presence of other specific antibodies, especially anti‐glycans. Protein or glycoprotein ICs (> 10 000 MW) are generally detected at low levels in VL or other leishmaniasis, such as post‐Kala‐azar dermal leishmaniasis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of assay limits the interaction of antibodies to proteins and glycoproteins, minimizing the presence of other specific antibodies, especially anti‐glycans. Protein or glycoprotein ICs (> 10 000 MW) are generally detected at low levels in VL or other leishmaniasis, such as post‐Kala‐azar dermal leishmaniasis …”
Section: Discussionmentioning
confidence: 99%
“…Protein or glycoprotein ICs (> 10 000 MW) are generally detected at low levels in VL 18 or other leishmaniasis, such as post-Kala-azar dermal leishmaniasis. 22,23 Structural composition of antigens complexed to IgG anti-leishmania antibodies is an important tool for the understanding of trigger mechanisms, permanence and elimination of ICs. Our search of low-molecular-weight antigens in PSE by sequential molecular exclusion chromatography revealed glycans (950-1800 MW) probably with 6-13 sugar residues by MALDI-TOF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have repeatedly suggested association of parasite infections with high levels of CICs which directly leads to tissue damage (Moulds et al, 1992). Previous studies from our lab have reported the presence of high levels of CICs among PKDL patients (Datta et al, 2015;Jaiswal et al, 2018). Further highthroughput studies are required to identify the specific peptide fragments from PKDL patients' CICs, representing specific proteins, which could act as glycated CICs proteome biomarker for both diagnostic and prognostic care of PKDL patients after treatment completion.…”
Section: Introductionmentioning
confidence: 76%
“…These studies highlight the role of proteomics in identifying disease specific protein markers that can help in detection of VL, when parasite load is scanty. Previous reports from our lab have reported altered CICs glycosylation status of PKDL patients (Datta et al, 2015;Jaiswal et al, 2018). High throughput proteomic analysis of PKDL patients' glycated CICs will assist in the identification of major PKDL disease specific protein biomarkers among Indian (MAC and POLY) PKDL population.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation